GSK3 inhibition with low dose lithium supplementation augments murine muscle fatigue resistance and specific force production. Issue 14 (29th July 2020) - Whitley, Kennedy C.; Hamstra, Sophie I.; Baranowski, Ryan W.; Watson, Colton J. F.; MacPherson, Rebecca E. K.; MacNeil, Adam J.; Roy, Brian D.; Vandenboom, Rene; Fajardo, Val A.
Abstract: Calcineurin is a Ca 2+ ‐dependent serine/threonine phosphatase that dephosphorylates nuclear factor of activated T cells (NFAT), allowing for NFAT entry into the nucleus. In skeletal muscle, calcineurin signaling and NFAT activation increases the expression of proliferator‐activated receptor‐gamma coactivator 1‐alpha (PGC‐1α) and slow myosin heavy chain (MHC) I ultimately promoting fatigue resistance. Glycogen synthase kinase 3 (GSK3) is a serine/threonine kinase that antagonizes calcineurin by re‐phosphorylating NFAT preventing its entry into the nucleus. Here, we tested whether GSK3 inhibition in vivo with low dose lithium chloride (LiCl) supplementation (10 mg kg −1 day −1 for 6 weeks) in male C57BL/6J mice would enhance muscle fatigue resistance in soleus and extensor digitorum longus (EDL) muscles by activating NFAT and augmenting PGC‐1α and MHC I expression. LiCl treatment inhibited GSK3 by elevating Ser9 phosphorylation in soleus (+1.8‐fold, p = .007) and EDL (+1.3‐fold p = .04) muscles. This was associated with a significant reduction in NFAT phosphorylation (−50%, p = .04) and a significant increase in PGC‐1α (+1.5‐fold, p = .05) in the soleus but not the EDL. MHC isoform analyses in the soleus also revealed a 1.2‐fold increase in MHC I ( p = .04) with no change in MHC IIa. In turn, a significant enhancement in soleus muscle fatigue ( p = .04), but not EDL ( p = .26) was found with LiCl supplementation. Lastly, LiCl enhanced specific force production in both soleus ( p < .0001) and EDL ( p = .002) muscles. Altogether, our findings show the skleletal muscle contractile benefits of LiCl‐mediated GSK3 inhibition in mice. Abstract :